Feasibility of HIV self-test implementation among Mizo youths: a field investigation from Northeast India bordering Myanmar - Rao, Amrita; Pachuau, Henry Zodinliana; Panda, Samiran; Chawngthu, Richard L.; Zomuanpuii, Rita; Hemade, Pranoti; Nirmalkar, Amit (Frontiers in Public Health, 2025)
IntroductionThis study investigated the potential of HIV self-test (HIVST) to reach individuals who otherwise might not access testing or antiretroviral therapy (ART). The study had two main objectives: (a) to develop an HIV self-test implementation plan based on the findings from qualitative inquiries with local stakeholders and (b) to examine HIVST uptake among youths in the urban setting of Aizawl district in Mizoram.MethodologyIn the first phase, qualitative in-depth interviews (IDI) were conducted with HIV program officials, religious leaders, community influencers, youths, and key population groups. These inquiries guided the planning of strategic communication, community engagement, HIVST delivery, and linkages with HIV confirmatory testing services in phase two. Factors associated with the non-uptake of HIV confirmatory tests by youths following HIVST were analyzed quantitatively. Additionally, secondary data collected from attendees of the “Integrated Counselling and Testing Centre” (ICTC) were also analyzed.ResultsThe in-depth interviews underscored the need to introduce HIVST among Mizo youths. The respondents emphasized the importance of diverse outreach approaches and communication strategies, including the use of social media platforms, as critical components for successful HIVST implementation. They also provided valuable insights on the optimal locations and methods for making HIVST kits accessible. Among the youths who used HIVST, the majority were first-time testers (1,772/2,101; 84.3%). Those diagnosed with an undiagnosed HIV infection were started on ART. The preference for the blood-based HIVST format (1,162/2101; 55%) was noted to be slightly higher than the saliva-based format. Confirmatory test uptake was significantly higher among those with sero-reactive HIVST results (χ2 23.89; p < 0.001). Factors independently associated with (adjusted odds ratio; AOR with 95% CI) “no-show for HIV confirmatory tests,” which hold significant programmatic implications, included “age > 20 years (1.47; 1.18–1.82),” “gender (men)” (1.25; 1.01–1.55), “education below 10th standard” (5.16; 2.66–10.01), “no prior HIV testing experience” (2.12; 1.61–2.81), and “unwillingness to undergo HIV confirmatory testing” (2.85; 2.05–3.96). Individuals who opted for the blood-based HIVST were 23% less likely (AOR 0.77; 95% CI; 0.62–0.96) to drop out of the HIV confirmatory testing process. Additionally, only 1% of respondents perceived HIVST as having self-harm potential.ConclusionSustained community engagement, effective networking with HIV program officials, and strategic communication were three critical pillars supporting the successful implementation of HIVST. There was a significant increase in HIVST uptake among young first-time testers.